Changes in inflammatory biomarkers related to C-reactive protein and albumin in patients with terminal cancer receiving palliative care: a longitudinal study. - Emanuelly Varea Maria Wiegert; Larissa Calixto Lima; Gabriella da Costa Cunha; Tais Saint Martin Fonseca; Geisiane Alves da Silva; Livia Costa de Oliveira (Brazilian Journal of Oncology)
Background: Evidence about how inflammatory biomarkers vary during the end-stage cancer trajectory is lacking. This study investigates the longitudinal changes in albumin and C-reactive protein (CRP) levels, and CRP/albumin ratio (CAR) in patients with terminal cancer receiving palliative care in the last three months of life.